(untitled) (Dimensión Antropológica, 2021)
In this article, I explore the cultural aspects that affect the exercise of rights of indigenous people, for this reason inquiry about the construction of indigeneity in the framework of the Costa Rican Judiciary and its effects in the justice and in the exercise of rights of indigenous people, in this order revised a series of sentences of the Costa Rican Constitutional Chamber and interview twelve judges, as a result of which it’s found that the application of a liberal law and a positivist legal culture make that national regulations is impose to the detriment of the indigenous regulations.